Gladys Black letter to Nicholas S. Halmi regarding bird sighting reports, March 18, 1977 - Black, Gladyset al (1977)
Letter from Gladys Black to Nicholas S. Halmi, regarding bird sighting reports. Sightings reported include a partially leucistic robin. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly Report of spring 1977. Epson - sheet feed/flatbed